A COMPARATIVE STUDY ON PHARMACEUTICAL EQUIVALENCE OF GENERIC AND BRANDED CARBAMAZEPINE TABLET - D.SHEELA,; C.B.THARANI, (International Journal of Pharma and Bio Sciences, 2015)
Generic drug are identical or bioequivalent to a branded drug in dosage form, safety, strength, route of administration, quality and performance characteristic and intended use. The advantage of generic drug is the low cost because they do not undergo any large expensive clinical trials like other formulations. In 2002 FDA,stated that the Americans saved 56.7 billion dollars and could save additional 1.32 billon dollars per year by using generic drugs. However, there are claims that generic drugs may differ in bioequivalence and likely to be either sub therapeutic or toxic to the patients. In our study we compared an anti epileptic drug namely, Carbamzepine generic drug with three different brand agents. Results of our study showed that individually generic drug and the branded drug complied with in the limit but dissolution, disintegration, friability, hardness test determined in pharmaceutical equivalence study showed statistically significant.